Tuber guizhouense sp. nov. (Tuberaceae, Ascomycota) from Guizhou Province, China - Wang, Jing; Yang, Yi Hua; Xiang, Zhun; Deng, Chun Ying (Phytotaxa, 2025)
Based on morphological and molecular phylogenetic evidence, a novel truffle species, Tuber guizhouense, is described from Populus-associated forests in Guizhou Province, China. This species is characterized by subglobose to globose ascomata (24–49 mm in diameter) with dark brown surfaces adorned by low pyramidal warts and occasional cracks. The mature gleba exhibits a marbled pattern with whitish veins. Ascospores are long-ellipsoid to cylindrical, bearing free spines (3–12 µm in height), and asci contain 1- spores. The combined phylogenetic analysis of ITS, 28S, and TEF1-α regions robustly support its distinctiveness (BS/PP = 100/1), placing it in a sister clade to the Japanese endemic T. longispinosum. Morphologically, T. guizhouense differs from related species (e.g., T. yigongense and T. sinense) by its pseudoparenchymatous peridium, unique spore ornamentation, and dark brown ascomata. This species represents the first wild truffle resource reported in Guizhou, occurring at altitudes of 1400–1500 m in symbiotic association with Populus trees, and is confirmed to be edibility. Its discovery expands the known subtropical distribution of Tuber and provides critical insights into the biodiversity, biogeography, and sustainable utilization of truffle resources in China.